Development and validation of an HPLC-MS/MS method for the detection of ketamine in Calliphora vomitoria (L.) (Diptera: Calliphoridae). (August 2018) - Magni, Paola A.; Pazzi, Marco; Droghi, Jessica; Vincenti, Marco; Dadour, Ian R.
Abstract: Entomotoxicology is a branch of forensic entomology that studies the detection of drugs or other toxic substances from insects developing on the decomposing tissues of a human corpse or animal carcass. Entomotoxicology also investigates the effects of these substances on insect development, survival and morphology to provide an estimation of the minimum time since death. Ketamine is a medication mainly used for starting and maintaining anesthesia. In recent years ketamine has also been used as a recreational drug, and occasionally as a sedating drug to facilitate sexual assault. In both activities, it has resulted in several deaths. Furthermore, ketamine has been also implicated in suspicious deaths of animals. The present research describes for the first time the development and validation of an analytical method suited to detect ketamine in larvae, pupae, empty puparia, and adults of Calliphora vomitoria L. (Diptera: Calliphoridae), using liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). This research also considers the effects of ketamine on the survival, developmental rate and morphology (length and width of larvae and pupae) of C. vomitoria . The larvae were reared on liver substrates homogeneously spiked with ketamine concentrations consistent with those found in humans after recreational use (300 ng/mg) or allegedly indicated as capable of causing death in either humans or animals (600 ng/mg). The results demonstrated that (a) HPLC-MS/MS method is applicable to ketamine detection in C. vomitoria immatures, not adults; (b) the presence of ketamine at either concentration in the food substrate significantly delays the developmental time to pupal and adult instar; (d) the survival of C. vomitoria is negatively affected by the presence of ketamine in the substrate; (e) the length and width of larvae and pupae exposed to either ketamine concentration were significantly larger than the control samples. Highlights: A HPLC-MS/MS method to detect ketamine in blowflies has been developed and validated. Ketamine may be detected in blowflies immatures by HPLC-MS/MS. Ketamine in the food substrate delays the total developmental time of blowflies. Ketamine affects the survival, the length and the width of immature blowflies.